2007
DOI: 10.1007/s11661-007-9423-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain Refinement on Structure Evolution, “Floating” Grains, and Centerline Macrosegregation in Direct-Chill Cast AA2024 Alloy Billets

Abstract: Direct-chill (DC) cast billets 192 mm in diameter of an Al-Cu-Mg alloy were examined in detail with the aim to reveal the effects of grain refining (GR) and casting speed on structure, ''floating'' grains, and centerline macrosegregation. Experimental results show that grain size and dendrite arm spacing (DAS) tend to coarsen toward the billet center with a local refinement DAS in the center. In GR billets, grain size does not change much with the cooling rate, casting speed, and grain refiner amount. Coarse-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…A detailed analysis of the structure is reported elsewhere [15], here only some relevant data are given. Addition of a grain refiner resulted in significant decrease in the grain size as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed analysis of the structure is reported elsewhere [15], here only some relevant data are given. Addition of a grain refiner resulted in significant decrease in the grain size as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The line scans were made through the selected grains with coarse and fine dendrite branches and the examples of such scans are given elsewhere [15]. In this paper we will focus on the analysis of results that can be extracted from the compositional profiles like those shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, higher casting speed and lower casting temperature result in a finer microstructure, [3][4][5] while cooling water-flow rate has relatively minor effect on grain structure. [6,7] The distribution of structure parameters in the horizontal section of a DC casting billet (along the radius or diameter) is of great importance since it determines the homogeneity of technological properties during downstream processing.…”
Section: Introductionmentioning
confidence: 99%
“…However, contrary to Mg, Mn shows negative segregation at the surface of the ingot. This phenomenon has not been seen before as Eskin et al [24], and Nadella et al [25] found positive segregation of Mn in DC cast ingots, while Dons et al [26] observed that manganese resists macrosegregation in DC cast Al-Si alloys. Finally Cr shows a positive segregation at the center, no segregation at the middle and negative segregation at the surface of the ingot.…”
Section: Segregationmentioning
confidence: 88%